1995
DOI: 10.1002/cne.903510109
|View full text |Cite
|
Sign up to set email alerts
|

In situ hybridization analysis of CHOT1, a creatine transporter, in the rat central nervous system

Abstract: A putative choline transporter (CHOT1) has been cloned from rat brain and is reported to express a high-affinity, sodium-dependent, hemicholinium-3-insensitive choline transporter in oocytes. A second transporter (OCCREATRA) cloned from rabbit brain is 98% homologous to CHOT1 and is reported to transport creatine. We examined the distribution of CHOT1 mRNA in rat brain by in situ hybridization, using a 48 base oligonucleotide probe. In adult rats, the hybridization signal was widespread, but with a distinct pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 35 publications
8
25
1
Order By: Relevance
“…The in vitro measurements of CK isoenzymes and CrT and the in vivo CK-catalyzed reaction rate constants in the developing rabbit cerebral gray matter and white matter allow a direct comparison to the recently published 31 P NMR measurements of the CK reactants PCr and ATP in these regions [15]. As previously seen in the rat, the relative ratio of Mi-CK to B-CK in gray matter is much higher than in white matter [4].…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The in vitro measurements of CK isoenzymes and CrT and the in vivo CK-catalyzed reaction rate constants in the developing rabbit cerebral gray matter and white matter allow a direct comparison to the recently published 31 P NMR measurements of the CK reactants PCr and ATP in these regions [15]. As previously seen in the rat, the relative ratio of Mi-CK to B-CK in gray matter is much higher than in white matter [4].…”
Section: Discussionmentioning
confidence: 54%
“…The CK-catalyzed reaction rate constants measured in vivo by 31 P NMR also showed regional differences in control and in Cr-treated rabbits (fig. 4, table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One may speculate that the need for large numbers of astrocytes may be caused by the high energy demand of hippocampal pyramidal neurons, which have a higher synaptic density per neuron than other neocortical neurons (19). It is also supported by high amounts of cytosolic or mitochondrial creatine kinase isoenzymes found in granular and pyramidal cell layers of the hippocampus during postnatal development of rats as well as by high levels of expression of the creatine transporter in the pyramidal cell layer of adult rat brains (20,21). In humans, there is even evidence of muscle-type creatine kinase in pyramidal cells of the hippocampus proper (22).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, mouse and rat CNS can take up Cr from the blood against its concentration gradient (Ohtsuki et al 2002;Perasso et al 2003). SLC6A8 is expressed throughout the main regions of adult mammalian brain (Schloss et al 1994;Happe and Murrin 1995;Braissant et al 2001b;Tachikawa et al 2008;Mak et al 2009). In the first detailed analyses of Cr transporter expression in CNS, it was demonstrated that SLC6A8 is found in neurons and oligodendrocytes but, in contrast to AGAT and GAMT, cannot be detected in astrocytes ( Fig.…”
Section: Agat Gamt and Slc6a8 In Cnsmentioning
confidence: 99%